Princely longing for Europe: Constantine II Brâncoveanu's Mogoşoaia Palace (1702) and the creation of a European identity - Cornea, Bogdan (European review of history = Revue européene d'histoire, 2014)
Trapped among the Austrian, Russian and Ottoman empires, the reign of Constantin II Brancoveanu, Prince of Wallachia, was a constant balancing act between the West and the East. To further his political and cultural ambitions, Constantin initiated and supported an artistic movement, known today as the Brancovenesc style, of which his residence, the Mogosoaia Palace, stands as a prime example. The architecture and ornamentation of the palace makes use of elements from both Eastern - Byzantine and Ottoman - and Western - Renaissance and Baroque - European artistic traditions, merging them into an organic whole. The aim of this article is to explore the artistic strategies employed throughout the palace by arguing that they explicitly, as well as implicitly, construct an inclusive European identity. Starting from the premise that the palace acted as a place of cultural encounter between the East and West, the analysis will focus on how the decoration implies a space of transition through subjects such as metamorphosis and the double-headed eagle. Also, the importance given to spaces such as the entrance foyer and loggia suggests their role as critical spaces evoking the ambiguous concept of the parergon, which in turn challenges the emerging Enlightenment idea of the West as properEurope and the East as not quite Europe.